2018
DOI: 10.1111/1471-0307.12516
|View full text |Cite
|
Sign up to set email alerts
|

A review of test protocols for the evaluation of teat disinfectants

Abstract: The prevention of mastitis is the most important part of a mastitis control programme. Postmilking disinfection is considered the most effective procedure for preventing new intramammary infections in dairy herds. This article reviews the different protocols used to evaluate the efficacy of teat disinfectant products. These protocols include experimental challenge, natural exposure and excised teat, along with agar diffusion assays and teat swabbing. The experimental designs, limitations, positive and negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(249 reference statements)
0
6
0
Order By: Relevance
“…In some cases, an increase in bacterial counts was observed after disinfection. This could be due to applying different pressures to the swab when sampling (Fitzpatrick et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In some cases, an increase in bacterial counts was observed after disinfection. This could be due to applying different pressures to the swab when sampling (Fitzpatrick et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…It has been suggested that an effective teat disinfectant should minimally yield a 3 log reduction in bacterial numbers, with a 4–5 log reduction being preferable (Fitzpatrick et al ., 2018). We did not observe more than a 3 log reduction in bacterial numbers in our study for either mesophilic or psychotrophic counts.…”
Section: Resultsmentioning
confidence: 99%
“…There were 4 treatment groups and one control: casein hydrolysate; casein hydrolysate + dry cow antibiotic (Dry-Clox, Boehringer Ingelheim, Ridgefield, CT, USA); casein hydrolysate + teat sealant (Orbeseal, Zoetis Animal Health, Parsippany, NJ, USA); casein hydrolysate + dry cow antibiotic + teat sealant; and dry cow treatment + teat sealant (control). One half of each udder, front and rear quarters combined, was randomized to a treatment group, while the other half received control, allowing every cow to serve as her own control and minimize the effect of variability between animals [ 23 , 24 ]. Study cows were marked with corresponding colored leg bands on both hind legs, along with an additional leg band used to identify the control side.…”
Section: Methodsmentioning
confidence: 99%
“…A review of test protocols for the evaluation of teat disinfectants is presented in the paper by Fitzpatrick et al (2021). Milkers should disinfect the udder teats before milking by immersing them in an approved disinfectant in order to reduce bacterial counts on the teat skin Gleeson et al, 2009;Baumberger et al, 2016;Fitzpatrick et al, 2018;Gleeson et al, 2018;Fitzpatrick et al, 2021). Nowadays, numerous preparations (iodine, chlorine, chlorhexidine -based and others) are available for disinfecting udder teats before cow milking.…”
Section: Premilking Hygiene Proceduresmentioning
confidence: 99%